The impact of regional development towards the well-being of rural community. Issue 1 (November 2021) - Yusoff, N S; Rashid, M F; Halim, N A
Abstract: Since before the British rule, the issues and problems of urban transformation growth have continued until today, especially in rural areas and small towns. Rural communities also have undergone significant transformations in recent decades. There are positive and negative impacts on adaptation the growth of regional development that impact significantly on the rural community, which needs to be addressed to overcome the adverse effects on those that involved. This also included the changes in a case study of rural areas that have been chosen, which is located in sub-district that categorize under rural areas at Johor Bahru due to Iskandar Malaysia region expansions. Furthermore, the developmental transformation has mainly affected the changes in the socio-economic well-being of rural communities. Therefore, the purpose of this paper is to provide an overview of studies on a factor of socio-economic well-being development in rural areas for creating a framework to measure the impact of regional development on the socio-economic well-being of the rural.